2017
DOI: 10.3389/fnut.2017.00003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Selected Microbial-Derived Phenolic Metabolites and Aroma Compounds from Wine in Human SH-SY5Y Neuroblastoma Cells and Their Putative Mechanisms of Action

Abstract: Moderate wine consumption has shown the potential to delay the onset of neurodegenerative diseases. This study investigates the molecular mechanisms underlying the protective effects of wine-derived phenolic and aroma compounds in a neuroinflammation model based on SIN-1 stress-induced injury in SH-SY5Y neuroblastoma cells. Cell pretreatment with microbial metabolites found in blood after wine consumption, 3,4-dihydroxyphenylacetic (3,4-DHPA), 3-hydroxyphenylacetic acids and salicylic β-d-O-glucuronide, at phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…ETs, which are abundant in pomegranates, berries, and nuts, are hydrolyzed into EA in the body after ingestion as a kind of water-soluble tannin, and hydrolyzed EA is metabolized by Uros [17,24,25]. ETs and EA have anti-inflammatory, antioxidant, and anti-cancer effects [26,27], but dietary EA has low bioavailability, due to its low solubility in the stomach and limited absorption in the intestine [14,[28][29][30]. González-Sarrías et al [31] reported that EA concentrations in the plasma or tissues do not exceed 100 nM, even after oral ingestion of pure EA at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETs, which are abundant in pomegranates, berries, and nuts, are hydrolyzed into EA in the body after ingestion as a kind of water-soluble tannin, and hydrolyzed EA is metabolized by Uros [17,24,25]. ETs and EA have anti-inflammatory, antioxidant, and anti-cancer effects [26,27], but dietary EA has low bioavailability, due to its low solubility in the stomach and limited absorption in the intestine [14,[28][29][30]. González-Sarrías et al [31] reported that EA concentrations in the plasma or tissues do not exceed 100 nM, even after oral ingestion of pure EA at high concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently reported that the health benefits of polyphenol-rich foods are mainly due to their gut microbial-derived metabolites, not their polyphenol compounds [12,13]. Polyphenols are converted into phenolic metabolites of small molecular weight by the action of gut microbiota in the small intestine; these gut microbial-derived metabolites have high bioavailability and permeability of the blood-brain barrier (BBB) [14].…”
Section: Introduction 1)mentioning
confidence: 99%
“…In addition to this, studies have found that quercetin 3-glucoside protected SH-SY5Y cells against hydrogen peroxide-induced oxidative stress and can also attenuate monoamine oxidase-A (MAO-A) activity in that cellular model. Finally, some authors have tested different polyphenol-derived metabolites in dopaminergic models against oxidative stress-induced cytotoxicity [ 21 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that acetate produced by protective Bifidobacteria could improve intestinal defense that is mediated by epithelial cells, and this could protect the host against negative infection (Fukuda et al, 2011). In addition, moderate consumption of wine has shown the potential to delay the onset of neurodegenerative diseases: After drinking, microbial metabolites may effectively protect neuroblastoma cells from nitrosative stress injury (Esteban-Fernandez et al, 2017).…”
Section: Close Relationships Among Diet Gut Microbiome and Health Carementioning
confidence: 99%